Natural Indicators of Borax and Its Utilization in the Development of Project-Based Student Worksheets to Improve Science Process Skills - Riva Ismawati*; Sunyoto Eko Nugroho; Agung Tri Prasetya (Universitas Syiah Kuala, 2023)
The foodstuff course is one of the subjects that is closely related to the context of daily life. The learning model that has been applied by lecturers has not been able to encourage students to use science process skills optimally and produce real work. The teaching materials used also have not trained students' skills and independence in solving problems of daily life. Borax is a prohibited additive in foodstuffs. This study aims to develop borax indicators from natural substances and develop project-based student worksheets to improve science process skills. The development of natural indicators of borax was carried out using the true experimental design method. Extracts of natural indicators were tested for color change in a solution of pH 5, 7, 12 and on positive and negative borax food samples. The development of student worksheets is carried out using a 4D (defining, designing, developing, and disseminating), model and is only limited to the stage through expert review. LKM that has been developed are validated by experts. The data obtained were then analyzed descriptively. The results showed that (a) extracts from secang wood and turmeric could be used as natural indicators of borax and (b) expert assessment of aspects of student worksheets obtained results in the high and very high validity ranges. The results of the development of natural indicators of borax can be used in the development of teaching materials. The developed student worksheets are suitable for limited testing